ANALYSIS OF STUDENTS’ ARABIC LANGUAGE ERRORS IN ACADEMIC ASSIGNMENTS: AN APPLIED LINGUISTICS REVIEW - Marwaji, Deden; Abdurrahman; Muslim, Ahmad Bukhori; Basyar, Syaripudin (Program Studi Pendidikan Bahasa Arab, 2025)
This study aims to identify and analyze phonological, morphological, syntactic, and semantic errors in the writing of students of the Arabic Language Education Study Program. Language errors in Arabic academic writing by students are a significant challenge in advanced Arabic language learning. The method used is qualitative analysis with a descriptive approach, based on the corpus of student writing data in the writing skills course. The results of the study showed that syntactic errors were the most dominant (37.5%), followed by morphological (29.2%), phonological (16.7%), and semantic (16.7%). The main causal factors include mother tongue interference, the use of literal machine translators, low understanding of Arabic grammar rules, and minimal contextual practice. The conclusion of this study emphasizes the need for an integrative and communicative learning approach, with an emphasis on authentic text-based exercises, contrastive analysis strategies, and the use of interactive learning media to improve students' linguistic accuracy in writing Arabic academic texts.